2023
DOI: 10.1021/jacs.2c13672
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Self-Immolative Bioresponsive MR Probes

Abstract: Real-time detection of bio-event in whole animals provides essential information for understanding biological and therapeutic processes. Magnetic resonance (MR) imaging represents a non-invasive approach to generating three-dimensional anatomic images with high spatial–temporal resolution and unlimited depth penetration. We have developed several self-immolative enzyme-activatable agents that provide excellent in vivo contrast and function as gene expression reporters. Here, we describe a vast improvement in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Hydrophilic gadolinium(III) contrast agents, often affectionately called "gado" by medical workers, 45 have greatly expanded the utility of MRI which is a noninvasive clinical tool without ionizing radiation. 46,47 They can shorten the longitudinal relaxation time (T 1 ) of water protons in their vicinity by virtue of the slow electron relaxations and fast water exchange kinetics of gadolinium(III) ions in the S = 7/2 ground state, therefore affording brighter MR signals. 48 In the design of novel Gd(III)-based MR contrast agents (GBCAs), there have been several long recognized design principles (vide infra) at the molecular scale for high relaxivity (r 1 ), mainly involving three intrinsic physical parameters: the hydration number (q), the rotational correlation time (τ R ) and the water exchange rate (1/τ m ).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Hydrophilic gadolinium(III) contrast agents, often affectionately called "gado" by medical workers, 45 have greatly expanded the utility of MRI which is a noninvasive clinical tool without ionizing radiation. 46,47 They can shorten the longitudinal relaxation time (T 1 ) of water protons in their vicinity by virtue of the slow electron relaxations and fast water exchange kinetics of gadolinium(III) ions in the S = 7/2 ground state, therefore affording brighter MR signals. 48 In the design of novel Gd(III)-based MR contrast agents (GBCAs), there have been several long recognized design principles (vide infra) at the molecular scale for high relaxivity (r 1 ), mainly involving three intrinsic physical parameters: the hydration number (q), the rotational correlation time (τ R ) and the water exchange rate (1/τ m ).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…While this approach is notably effective for the controlled release of drugs, its applications extend beyond pharmaceuticals into diverse fields, ranging from the design of selfdegrading polymers to the release of probes for sensing. [5][6][7][8][9][10] For example, in the realm of self-degrading polymers, [11][12][13][14] this strategy enables the decomposition of polymers in response to a specific stimulus, yielding their constituent building blocks. This innovation presents a promising solution to address environmental concerns related to the degradation of synthetic plastic materials.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] We have previously reported that the carbamate-toamine conversion in DO3A-pyridine-based Ln 3 + complexes (LnL 6 , Scheme 1) [25] induces remarkable variations in the luminescence intensity and in the CEST signals for Tb 3 + and Yb 3 + complexes, and in the relaxivity of the Gd 3 + analogue. The use of a self-immolative benzyl carbamate [26][27][28][29][30][31] can render such systems responsive to molecular events such as enzymatic cleavage.…”
Section: Introductionmentioning
confidence: 99%